REPORT ON THE EXPERIENCE OF IMPLEMENTING RADIOGRAPHIC DOWSING IN THE INTEGRATIVE MEDICINE OUTPATIENT CLINIC - INTEGRATIVE AND COMPLEMENTARY PRACTICES AT A HOSPITAL IN THE CITY OF SÃO PAULO - Suzin, Joseli Beatriz; Coelho, Juliane Cristina Burgatti; Otani, Alice Hiroko; Costa Neto, Eduardo Campos (Seven Editora, 2026)
This experience report describes the implementation of Radiesthesia and Radionics (RR) in an Integrative Medicine - Integrative and Complementary Health Practices (MI-PICS) outpatient clinic in the city of São Paulo. Initiated in February 2025, the initiative encompasses services for inpatients and outpatients, in face-to-face, online, and remote modalities. It was identified that RR acts by accessing information codes through instruments that decode bioenergetic signals. The integration between physiology and bioenergetics offered theoretical support for understanding the mental and spiritual dimensions as modulators of physical health, removing the stigma of subjectivity from these spheres and bringing them closer to evidence-based psychosomatic clinical practice.